The state of human rights disclosure among sustainably certified palm oil companies in Malaysia. Issue 10 (25th November 2020) - Wahab, Andika
ABSTRACT: There is a growing number of multinational companies disclosing their formal commitment to respect human rights. This derives partly from the escalation of various intergovernmental-led and market-based initiatives that urge companies and their suppliers to disclose human rights commitment and performance. Malaysia is the world's second-largest palm oil producer supplying to many global brands around the world. As such, palm oil companies in Malaysia are bound by the global market requirements to disclose their commitment to addressing human rights issues. Based on 16 samples among sustainably certified palm oil companies in Malaysia, this study argues that while human rights are becoming a common feature in their public disclosure, they lack further elaboration and substance. In most cases, companies do not disclose human rights risks they face and efforts undertaken to mitigate such risks, as well as the impacts of their business operations to the affected stakeholders. This raises concerns regarding their motives of disclosure and corporate accountability in addressing actual and potential human rights violations in the business sector.